The comparison of two procurement strategies in the presence of supply disruption. (July 2015) - He, Bo; Huang, He; Yuan, Kaifu
Highlights: Two types of procurement strategies under competition are investigated. The joint pricing and ordering decisions of duopoly are analyzed. The reliability threshold is derived to characterize the equilibrium outcomes. Solution procedures are proposed to determine the equilibrium outcomes. Abstract: The emergency procurement strategy and the optimal allocation procurement strategy are widely used for managing supply disruption risks. In this paper, we investigate two competing manufacturers using these procurement strategies in the presence of supply disruption risks. The joint pricing and ordering decisions of both manufacturers are analyzed using the game theoretic framework. The structural property of the manufacturer with the optimal allocation procurement strategy is characterized by the reliability threshold value, which further determines the equilibrium outcomes for both manufacturers. We find the reliability threshold is a generalization of the supplier's reliability level, which involves all the critical factors that influence manufacturers' procurement decisions under a competitive scenario. The optimal allocation procurement strategy for manufacturer profit maximization in a non-competitive scenario does not necessarily generate competitive advantage in a competitive scenario; under a wide range of parameters, the emergency procurement strategy can produce larger profit for the manufacturer than the optimal allocation procurement strategy when all suppliers are unreliable. The effects of reliability level and costs on procurement decisions are examined using comparative studies and numerical computations.